REVIEW: POTENSI KAYU MANIS SEBAGAI ANTIDIABETES - Utari, Roly Rahmah; Suryani (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Cinnamon has long been used in traditional medicine and is gaining increasing attention in modern scientific circles due to its bioactive compounds, such as cinnamaldehyde, polyphenols, and flavonoids, which play a role in antihyperglycemic effects and improving insulin sensitivity. Several clinical trials have shown that cinnamon supplementation (1–6 grams per day for 8–16 weeks) can reduce fasting blood glucose levels by 10–29 mg/dL and HbA1c by 0.4–0.7% in patients with type 2 diabetes.This study aims to evaluate the potential of cinnamon as an antidiabetic agent by reviewing scientific evidence related to its mechanism of action, effectiveness, and safety of long-term consumption. A literature search was conducted through the PubMed and Google Scholar databases using the keywords “Cinnamon” AND “Antidiabetes” for articles published in the period 2003–2023. The included articles included in vitro, in vivo, and clinical trial experimental studies, while review articles and meta-analyses were excluded. A total of 30 articles that met the criteria were analyzed descriptively.The review results suggest that cinnamon works through the mechanism of inhibiting the enzyme α-glucosidase and increasing insulin sensitivity, which contribute to lower blood glucose and HbA1c levels. However, heterogeneity in the type of cinnamon used, variation in dosage, method of consumption, and the lack of long-term studies on its safety are limitations that need to be considered. Therefore, further research is needed, especially large-scale clinical trials with longer duration, to confirm the efficacy and safety of cinnamon in the management of diabetes.